Enfrentamento de enfermeiros durante as três ondas da pandemia de covid-19 na atenção primária à saúde de um município cearense - Araújo, Jordanna Correia de (2023)
The COVID-19 pandemic by the new human coronavirus (SARS-CoV-2) has been one of the greatest health challenges on a global scale this century. Nurses, together with other health professionals, did not fail to fulfill their duty and kept their jobs, acting directly or indirectly on the front line against the disease. In Brazil, the first cases were confirmed in February, and several actions were implemented in order to contain and mitigate the advance of an emerging disease, highly transmissible, without vaccine or adequate treatment. Even so, nurses maintained their care routine and commitment to the population, working in several areas, including primary care. Objective: To identify the challenges faced by nurses inserted in Primary Health Care in the face of the covid- 19 pandemic in Mombaça/Ceará. Method: This is a qualitative research through the collection of information through semi-structured interviews and participant observation. The study was carried out in the municipality of Mombaça Ceará, in the first half of 2022. The population consisted of nurses who work in Primary Health Care in that municipality. Data analysis was through Bardin's content analysis and the Wordclouds tool. The construction was carried out by question, so each question generated a word cloud. Results: 14 nurses participated in the study, 4 men and 10 women. Everyone was in home isolation for safety. 4 clouds were generated, from which the words stood out: in cloud 1- Nursing; cloud 2- Assistance; cloud 3- Fear; cloud 4- Hypertensive. Conclusion: The nurses continued their work at the UBS despite the risk of becoming ill or contaminating the family. The study points out that the maintenance of UBS services is maintained with the presence of the professional nurse.